أثر تخطيط الموارد البشرية على أداء المنظمات - دراسة تطبيقية على شركة الواحة للنفط بطرابلس - الشريقي, أبوعجيلة (Al-Qurtas, 2025)
أثر تخطيط الموارد البشرية على أداء المنظمات - دراسة تطبيقية على شركة الواحة للنفط بطرابلس